2019
DOI: 10.1002/cctc.201901239
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ One‐Step Preparation of Nickel‐Tipped N‐doped Carbon Nanotubes for Oxygen Reduction

Abstract: Here, we successfully synthesized N-doped carbon nanotubes embedded with nickel-based nanoparticles on the top (N-CNTs/ E-NNPs) by directly procedural calcination of melamine and nickel foam at 520°C, 540°C and 700°C in Ar. When applied for oxygen reduction reaction (ORR), the onset potential and halfwave potential are 0.96 V and 0.86 V in 0.1 M KOH, comparable to that of the commercial 10 wt% Pt/C. Moreover, the hybrids possess higher stability and better methanol tolerance. Additionally, the Tafel slope of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Occasionally, we have found in experiments that Ni electrodes (Ni foam or Ni mesh, widely exploited as the supporting substrate for nanostructured electrocatalysts toward nitrate, ,, carbon dioxide, , or oxygen reduction ) can be self-activated after consecutive cycles during NO 3 RR, exhibiting outstanding performance in nitrate-to-ammonia conversion with appreciably high selectivity, longevity, and Faradaic efficiency. Its role in facilitating NO 3 RR has been generally overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, we have found in experiments that Ni electrodes (Ni foam or Ni mesh, widely exploited as the supporting substrate for nanostructured electrocatalysts toward nitrate, ,, carbon dioxide, , or oxygen reduction ) can be self-activated after consecutive cycles during NO 3 RR, exhibiting outstanding performance in nitrate-to-ammonia conversion with appreciably high selectivity, longevity, and Faradaic efficiency. Its role in facilitating NO 3 RR has been generally overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Very recent studies on metal and N‐codoped graphene/carbon nanostructures showed great promise that these materials can replace Pt in fuel cell ORR catalysis [10,14] . Various experimental and theoretical studies have been performed on PGM‐free nanostructure with Mn, Fe, Co, Ni, and Cu metal centers, and the observed activities have been found to be comparable to that obtained with the standard Pt catalyst [10,14–25] . However, the durability of PGM‐free systems is still significantly lower than that of Pt catalysts [26,27] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 14 ] Various experimental and theoretical studies have been performed on PGM‐free nanostructure with Mn, Fe, Co, Ni, and Cu metal centers, and the observed activities have been found to be comparable to that obtained with the standard Pt catalyst. [ 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] However, the durability of PGM‐free systems is still significantly lower than that of Pt catalysts. [ 26 , 27 ] Most studies of PGM‐free ORR catalysts have focused on Fe‐ and Co‐based nitrogen‐doped carbons obtained by pyrolysis from molecular precursors.…”
Section: Introductionmentioning
confidence: 99%
“…S4a‐d). [ 42 ] Additionally, E‐NiCo 2 S 4 /SBS‐NCNTs have rigid characteristics, a distinct bamboo shape, and more uniform diameter of carbon nanotube. Due to the possible synergistic effect between melamine and surface‐nanosized nickel foamed, uniform encapsulated NiCo 2 S 4 ‐based nitrogen‐doped carbon nanotubes with straight bamboo shape can still be obtained in the absence of exogenous reducing gas, such as H 2 .…”
Section: Resultsmentioning
confidence: 99%